Conocimientos y prácticas de prevención del virus del papiloma humano en estudiantes del Colegio Nocturno Pío Jaramillo Alvarado - Quishpe Malla, Yadira Irene (2015)
The human papilloma virus is one of the most common infections of sexual transmission, there are more than 100 HPV types, in relation to their cancer pathogenesis, are classified as types of high and low cancer risk is passed on through genital contact and skin contact, it can infect any sexually active person. This research work was to determine the knowledge and prevention practices on human papillomavirus that have night school students Pio Jaramillo Alvarado ". The work is descriptive. The technique used to collect information was the survey that was applied to 80 participants. The results show that over 60% of respondents have no knowledge about the virus, known as its definition, forms of contagion, affected by sex, risk factors, injury and producing vaccines to prevent infection. A high percentage (60%) lack of knowledge about prevention measures in both sexes. Young female adopt good practices on prevention as: having sex with the same partner, condom use in all your relationships, be sober under any influence of alcohol and drugs, limiting the number of sexual partners, avoid risk sex without a condom. While males over 60% have inadequate determines as to preventing human papilloma virus in sex practices. KEYWORDS: human papilloma virus, prevention of human papillomavirus, knowledge of human papilloma virus.